MY NAME IS SPOT : LADYBIRD READERS - Eric ; Hill (LADYBIRD PUBLICATION, 2018)
Ladybird Readers is a graded reading series for English Language Teaching (ELT) markets, designed for children learning English as a foreign or second language. Ask, What$1 (Bs your name? with Spot. Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Recommended for children aged 4+, the five levels of Readers and Activity Books follow the CEFR framework (Pre-A1 to A2) and include language activities that help develop key skills and provide preparation for the Cambridge English: Young Learners (YLE) exams. Start with Spot introduces children to early conversational phrases and vocabulary.s